The Framingham cardiovascular risk score in multiple sclerosis. (27th April 2015) - Moccia, M.; Lanzillo, R.; Palladino, R.; Maniscalco, G. T.; De Rosa, A.; Russo, C.; Massarelli, M.; Carotenuto, A.; Postiglione, E.; Caporale, O.; Triassi, M.; Brescia Morra, V.
<x xml:space="preserve">Abstract</x> Background and purpose Cardiovascular risk factors can increase the risk of multiple sclerosis (MS) and modify its course. However, such factors possibly interact, determining a global cardiovascular risk. Our aim was to compare the global cardiovascular risk of subjects with and without MS with the simplified 10‐year Framingham General Cardiovascular Disease Risk Score (FR) and to evaluate its importance on MS‐related outcomes. Methods Age, gender, smoking status, body mass index, systolic blood pressure, type II diabetes and use of antihypertensive medications were recorded in subjects with and without MS to estimate the FR, an individualized percentage risk score estimating the 10‐year likelihood of cardiovascular events. Results In total, 265 MS subjects were identified with 530 matched controls. A t test showed similar FR in cases and controls (P = 0.212). Secondary progressive MS presented significantly higher FR compared to relapsing−remitting MS (P < 0.001). Linear regression analysis showed a direct relationship between FR and Expanded Disability Status Scale (P < 0.001) and MS Severity Scale (P < 0.001). Conclusion The FR, evaluating the global cardiovascular health by the interaction amongst different risk factors, relates to MS disability, severity and course.